2013
DOI: 10.1200/jco.2011.39.5137
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Study of Bortezomib, Thalidomide, and Dexamethasone With or Without Cyclophosphamide As Induction Therapy in Previously Untreated Multiple Myeloma

Abstract: Both VTD and VTDC are highly active induction regimens producing high combined CR/nCR and MRD-negative rates; however, VTDC was associated with increased toxicity and suggestion of transient decreases in Global Health score, without an increase in activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 35 publications
9
69
0
Order By: Relevance
“…In our evaluation of CyBorD use in a non-trial setting, we were able to confirm the high efficacy of once weekly CyBorD with an ORR 95% and ⩾ VGPR rate of 66%, comparable to results from the original CyBorD phase 2 data published by Reeder et al (Table 4), as well as to other three-and four-drug combinations in the literature. [9][10][11][12][13]16 Of note, CyBorD outcomes appear comparable to that of VRD (bortezomib, lenalidomide and dexamethasone) and VTD (bortezomib, thalidomide and dexamethasone), two of the most effective induction regimens reported with ORR of 100 and 93-95%; ⩾ VGPR of 67% and 60-62%, respectively. 3,9,10 Comparison of induction response among three-and four-drug regimens is summarized in Table 6.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In our evaluation of CyBorD use in a non-trial setting, we were able to confirm the high efficacy of once weekly CyBorD with an ORR 95% and ⩾ VGPR rate of 66%, comparable to results from the original CyBorD phase 2 data published by Reeder et al (Table 4), as well as to other three-and four-drug combinations in the literature. [9][10][11][12][13]16 Of note, CyBorD outcomes appear comparable to that of VRD (bortezomib, lenalidomide and dexamethasone) and VTD (bortezomib, thalidomide and dexamethasone), two of the most effective induction regimens reported with ORR of 100 and 93-95%; ⩾ VGPR of 67% and 60-62%, respectively. 3,9,10 Comparison of induction response among three-and four-drug regimens is summarized in Table 6.…”
Section: Discussionmentioning
confidence: 89%
“…The absence of grade 3-4 peripheral neuropathy is remarkable and compares favorably with rates of this complication associated with other novel agent combinations, specifically 10% with VTD (bortezomib, thalidomide and dexamethasone), 13% with VRCD, and 8% with VTCD (bortezomib, thalidomide, Cy and dexamethasone). 3,12,16 CyBorD is convenient and easy to administer with the bortezomib in a once-weekly schedule. Moreover, the current standard of care has moved from an i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported encouraging results for MM patients with BCD regimen [19,[24][25][26], in both newly diagnosed and relapsed/refractory patients, including patients of all ages. The ORR ranged from 69 to 96 %.…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib was also evaluated in combination with cyclophosphamide and dexamethasone (BCD) in newly diagnosed MM patients, both eligible and ineligible for ASCT [18]. Nevertheless, BCD regimens were inevitably associated with increased toxicity, resulting in a transient decrease in the global health score [19].…”
Section: Introductionmentioning
confidence: 99%
“…There is no evidence that 4-drug regimens are superior and they may be more toxic. 19,20 The better response rate observed with new regimens is 21 36 38 n/a related to a better efficacy across all prognostic subgroups, including ISS 3 and poor-risk cytogenetics. 6,12 There is currently no direct evidence that the higher CR plus n-CR rate achieved with these new regimens translates into a longer PFS since in all of these studies, there were different post-ASCT treatments.…”
Section: What Is the Best Induction Treatment Prior To Autologous Stementioning
confidence: 99%